Cancer information for children: effect on adherence to intramuscular chemotherapy - Amaral, Mariana; Zoéga Soares, Maria Rita; Gioia, Paula Suzana (Psicooncología, 2017)
Objective. The purpose of this study was to verify the effects of an intervention that involved providing cancer information to children. The intervention targeted children’s adherence to treatment as well as competing behaviors that interfered with the chemotherapy.Method. A 9-year-old girl and a 4-year-old boy participated in the study, both diagnosed with acute lymphoblastic leukemia and undergoing ambulatory chemotherapy. The participants’ chemotherapy sessions were filmed before, during and after intervention, in a total of 16 sessions. The intervention, carried out individually for each participant throughout three sessions, was based on the book Estou doente, e agora? Orientações para crianças com câncer (I’m ill, what now? Orientations for children with cancer), which was organized into 24 cards containing information, recreational activities and other exercises for expressing feelings about the illness and its treatment. The recordings were watched by blind observers who recorded the occurrence of adherence and competing responses, both defined in accordance with an adapted version of the Observation Scale of Behavioral Distress (OSBD).Results. The results showed that the intervention was effective. During intervention, the frequency of the children’s adherence behaviors increased, while the frequency of their competing behaviors decreased. However, these effects were not maintained in post-intervention sessions.Conclusions. This is an intervention model that can be the basis for new studies attempting to plan increasingly better contingencies in order to develop a behavioral repertoire that is adaptive to this condition. The future studies should use a larger number of sessions and participants and adopt group interventions
Keywords: Adherence behavior; cancer; children; information.